PERBEDAAN HASIL BELAJAR TEMA 9 SUB TEMA 1 ANTARA MODEL PBL DAN PENDEKATAN SAINTIFIK DI KELAS IV - tifani, mutia; silvinia, silvinia; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research aims at finding out a significant difference of students’ learning outcomes in learning subtheme 1 of theme 9 between the PBL Model and the Scientific Approach at Class IV of SD Wilayah IV Guguak Panjang. This quasi experiment applied the probability sampling technique in selecting the sampel. They were 72 students out of 277 in toltal. Data were gathered by using a multiple-choice test. The hypotesis of the research was analysed by using the t-test formula. Based on the t-test of the students’ posttest scores, it was found that tcount > ttabel, (5,7285 > 1,66) with α = 0.05. Thus, H0 is rejected. The average score of the experimental class was 85,13 while the average score of the control class is 80,53. Ha is accepted which means that the PBL Model is better compared to the scientific approach.  Keywords: the PBL Model, Learning Outcomes, the Subtheme 1 of Theme 9